Analisis Daya Saing Produk Pertanian Lokal dalam Mendukung Agribisnis Berkelanjutan di Pedesaan - Andi Pratama; Siti Nurhaliza (Primary Journal of Multidisciplinary Research, 2026)
The competitiveness of local agricultural products is one of the key factors in supporting the sustainability of the agribusiness sector, particularly in rural areas where most communities still depend on agricultural activities as their primary source of livelihood. This study aims to analyze the competitiveness of local agricultural products and identify the factors influencing the improvement of such competitiveness in supporting sustainable agribusiness development in rural areas. The research employed a descriptive quantitative approach supported by qualitative analysis to provide a deeper understanding of field conditions. The results indicate that the competitiveness of local agricultural products is significantly influenced by several major factors, including product quality, production efficiency, market access, and the availability of agricultural infrastructure. Agricultural products that maintain high and consistent quality standards tend to compete more effectively in both local and regional markets. However, several challenges remain, such as the low adoption of modern agricultural technologies, limited farming capital, and weak distribution systems, which reduce the ability of local products to compete with agricultural products from outside the region. Furthermore, farmer institutions, such as cooperatives and farmer groups, have been proven to make a significant contribution to strengthening farmers' bargaining position in the market. The integration of digital technologies in marketing and agribusiness systems also has a positive impact on improving supply chain efficiency and expanding market access. In the context of sustainability, the development of local-based agribusiness should equally consider environmental, social, and economic aspects in order to provide long-term benefits for rural communities. In conclusion, enhancing the competitiveness of local agricultural products depends not only on production aspects but also on institutional strengthening, technological innovation, and government policies that support small-scale farmers. With appropriate strategies, rural agribusiness can develop sustainably and significantly improve community welfare.